A Matrix Method for Determining Eigenvalues and Stability of Singular Neutral Delay-Differential Systems - Jian Ma; Baodong Zheng; Chunrui Zhang (Journal of Applied Mathematics)
The eigenvalues and the stability of a singular neutral differential system with single delay are considered. Firstly, by applying the matrix pencil and the linear operator methods, new algebraic criteria for the imaginary axis eigenvalue are derived. Second, practical checkable criteria for the asymptotic stability are introduced.